Characterization of a lytic Escherichia coli phage CE1 and its potential use in therapy against avian pathogenic Escherichia coli infections - Tang, Zhaohui; Tang, Ning; Wang, Xinwei; Ren, Huiying; Zhang, Can; Zou, Ling; Han, Lei; Guo, Longzong; Liu, Wenhua (Frontiers in Microbiology, 2023)
High incidence in poultry caused by Avian pathogenic Escherichia coli has brought great economic losses. The alarming increase in antibiotic resistance has led to an urgent need for alternative therapeutic approaches. Phage therapy showed promising results in many reports. In our study, a lytic phage vB_EcoM_CE1 (short for CE1) was isolated from broiler feces, which displayed a wide host range of lysing 56.7% (33/58) of multidrug-resistant APEC strains. Morphological observation and phylogenetic analysis suggested that phage CE1 is a member of the genus Tequatrovirus, belonging to Straboviridae family with an icosahedral capsid (80~100 nm in dimeter) and a retractable tail (120 nm in length). phage CE1 had good pH (4~10) and temperature tolerance (＜60 ℃). Whole genome sequencing revealed that phage CE1 harbored 167, 955 bp linear double-stranded DNA genome with average GC content of 35.4%, including 271 predicted ORFs and 8 tRNAs. No genes associated with virulence, drug-resistance, or lysogeny were found in the genome. In vitro test showed that phage CE1 had high bactericidal activity against E. coli at a wide range of MOIs, and exhibited good effect on air spray and water disinfection. In vivo test indicated that phage CE1 had perfect protection for broilers challenged with E. coli. The current study provides some basic information for further research on treatment of colibacillosis, or acting as a disinfectant to kill E. coli in breeding environment.